anonymous
  • anonymous
Could someone help me figure out how to solve the rest of this? I need to find fog.. This is the initial equation: f(x)=x+7 and g(x)=3x+2 This is as far as I've gotten: fog = f(g(x)) = x(3x - 2)+7 Have I done this right so far? What do I do next? I have notes on this but I don't really understand how to do the next steps.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
I think I may have just figured it out....
zepdrix
  • zepdrix
f composed of g.. hmm i think you're very close :) f(g(x)) So if g(x)=3x+2 then f(g(x))=f(3x+2) If f( ) = ( ) + 7 fill in the blank! :)
anonymous
  • anonymous
Here's what I did: 1. f(x)=x+7 and g(x)=3x+2 2. fog=f(g(x))=x(3x-2)+7 3. fog=3x+2+7 (I switched from negative to positive/plus to minus) 4. Subtract 2 from itself and from 7 5. fog = 3x+5 Correct?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

NoelGreco
  • NoelGreco
f(3x+2) means that you replace the x in function f with 3x+2
NoelGreco
  • NoelGreco
Also, in step 2 you've got 3x MINUS 2, not 3x+2
zepdrix
  • zepdrix
f(x)= (x) + 7 f(x+y)= (x+y) + 7 f(potato)= (potato) + 7 whatever is inside of f, that's what you plug in for your original x. f(3x+2)= (3x+2) + 7 Does that make sense? :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.